2007
DOI: 10.1111/j.1471-4159.2007.05183.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of post‐mortem‐induced changes to the mouse brain proteome

Abstract: This study was designed to assess the influence of high-energy head-focused microwave irradiation and the post-mortem interval on measurements of the mouse brain proteome. Difference gel electrophoresis was used to compare mouse brain protein levels in animals killed by decapitation, where the tissue was held at 25 degrees C for selected time intervals post-mortem, and by high-energy head-focused microwave irradiation followed by immediate resection. Microwave-mediated killing was used because it comprehensive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
33
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 88 publications
0
33
0
Order By: Relevance
“…If properly done, one can detect a statistically signiWcant diVerence in the levels of particular proteins in the order of 10-20%. Clearly, this sensitivity is suYcient to detect changes proportional to gene dosage (Unlü et al 1997;Hunsucker et al 2008).…”
Section: Changes In the Proteome And Dsmentioning
confidence: 99%
See 1 more Smart Citation
“…If properly done, one can detect a statistically signiWcant diVerence in the levels of particular proteins in the order of 10-20%. Clearly, this sensitivity is suYcient to detect changes proportional to gene dosage (Unlü et al 1997;Hunsucker et al 2008).…”
Section: Changes In the Proteome And Dsmentioning
confidence: 99%
“…For example, for some proteins, especially phosphoproteins, time postmortem can be critically important. Hunsucker et al (2008) compared the brain proteome of mice euthanized by decapitation and rapid dissection with euthanasia using high energy focused microwave application to the brain, which is thought to snap-inactivate enzyme activities in the brain. They found that while most proteins were stable for 4 h, a subset of 3.8% of proteins showed changes depending upon the method of euthanasia, and 4.8% showed changes over the postmortem interval studied (4 h).…”
Section: Changes In the Proteome And Dsmentioning
confidence: 99%
“…The sensitivity of total lysate 2D-DIGE is too low and too few proteins were identified in order to be certain that these spot families encompass all isoforms of any given protein, which seems unlikely anyway. It seems more reasonable that the spot families represent an altered PTM status such as phosphorylations, as described for dynamin-1 in post mortem mouse brain tissue (12). The general level of sample procedure induced differential intensity between the samples, with the exception of some few proteins, lies within Ϯ 100% for the proteomes (Fig.…”
Section: Discussionmentioning
confidence: 73%
“…5 and 6). Muscle and brain are the most characterized tissues with regard to post mortem degradation, with most proteomics studies focused on brain tissue (1,(3)(4)(5)(11)(12)(13)(14)(15)(16). Several proteins found in the brain degradome were also detected in the liver or pancreas degradome (Table III, IV).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation